Vagaries of News Translation on Canadian Broadcasting Corporation Television: Traces of History - Conway, Kyle (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2014)
This article describes a series of failed attempts by the English and French networks of the Canadian Broadcasting Corporation to present translated news. On one level, it is concerned with the impulse that prompts people during moments of crisis to suggest translated news as a solution to a problems related to Canadian identity and the reasons their suggestions to translate news programs are not acted upon. On a deeper level, it is concerned with a methodological and epistemological problem facing translation historians: what happens when the relevant documents are not preserved because journalists’ notions of translation differ from those of historians? It recommends that historians turn to “para-archives,” or collections created and preserved by non-news organizations, that contain descriptions of the documents journalists have not kept. These para-archives can provide evidence for the creation of plausible narratives about the competing interests shaping decisions not to produce translated news. They can also reveal how historians actively produce the categories they use to define their object of study.